EVALUASI DAN ANALISIS PENERAPAN KURIKULUM MERDEKA DI SEKOLAH MENENGAH ATAS - Hadi Siswanto, Deny; Kintoko (LPMP Provinsi DKI Jakarta, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum for 10th-grade students at SMA Muhammadiyah Mlati. The research involved 18 teachers and 72 10th-grade students as the population, with all students selected as the sample using a total sampling technique. A quantitative approach with descriptive data analysis was employed. Data were collected through observation, interviews, observation questionnaires, and document analysis related to the curriculum's implementation. The findings indicate that the implementation of the Merdeka Curriculum at SMA Muhammadiyah Mlati has been successful, as reflected by the majority of respondents rating it as “Excellent” in the distributed questionnaires. This suggests that the curriculum has been applied effectively. These results are consistent with previous studies that highlight the benefits of personalized learning approaches in helping students catch up more efficiently. With continued support from various stakeholders, the implementation of the Merdeka Curriculum is expected to become more optimal and contribute positively to the advancement of education at SMA Muhammadiyah Mlati